2010
DOI: 10.1103/physrevb.81.094423
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of magnetic ordering in single-crystallineU2NiSi3

Abstract: Single crystal of ternary uranium-based silicide U 2 NiSi 3 , which crystallizes with a disordered hexagonal AlB 2 -type structure, was investigated by means of magnetic, resistivity, heat capacity, and neutron-diffraction measurements. While dc magnetic characteristics and neutron-diffraction measurement give evidence for the long-range magnetic ordering, ac magnetic susceptibility, isothermal remanent magnetization, resistivity, and heat capacity data are consistent with spin-glass behavior. The obtained res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 21 publications
(28 reference statements)
7
15
0
Order By: Relevance
“…It is generally known that dc-magnetization in the field cooled condition of canonical spin-glass systems is nearly independent of temperature below T * . 34) In contrast, the continuous enhancement of the dc-magnetization is frequently observed below T * in the cluster-glass system, [51][52][53][54] and it closely resembles the present observations for x ≥ 0.3. In particular, the overall temperature dependence of the dc-magnetization, frequency dependences of T * and amplitude χ ′ ac at T * are very similar to those of the CeNi 1−x Cu x system.…”
Section: Discussionsupporting
confidence: 90%
“…It is generally known that dc-magnetization in the field cooled condition of canonical spin-glass systems is nearly independent of temperature below T * . 34) In contrast, the continuous enhancement of the dc-magnetization is frequently observed below T * in the cluster-glass system, [51][52][53][54] and it closely resembles the present observations for x ≥ 0.3. In particular, the overall temperature dependence of the dc-magnetization, frequency dependences of T * and amplitude χ ′ ac at T * are very similar to those of the CeNi 1−x Cu x system.…”
Section: Discussionsupporting
confidence: 90%
“…The results corroborated the ferromagnetic behaviour reported in Ref. [5] and additionally veried the absence of impurity phase UNiSi 2 that was observed in our previous study [6].…”
Section: Methodssupporting
confidence: 81%
“…In the latter study, the polarized neutron diraction measurement revealed that the uranium magnetic moments of 0.6 µ B are oriented in the ferromagnetic state perpendicular to the c-axis. Most recently, thermodynamic, electrical transport and neutron diraction measurements of single-crystalline U 2 NiSi 3 conrmed the ferromagnetic ordering below 26 K, with the uranium magnetic moments of 1.05 µ B [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature indicates that the magnetic moments in U 2 RhSi 3 are probably confined within the basal hexagonal plane. Similar spin arrangement was observed in closely related compounds such as U 2 NiSi 3 [22,5]) and U 2 PdSi 3 [11]. Fig.…”
Section: Magnetic Propertiessupporting
confidence: 72%